Cholesterol and physical activity in the Covid-19 pandemic in students of the IV cycle of Obstetrics at Roosevelt University - Pilco Villagra , María Del Carmen (2022)
Introduction: Cholesterol is considered the main human steroid, highlighting that cholesterol is not harmful because it is a molecule that participates in vital processes for humans, however an excessive increase in cholesterol levels can be detrimental to health, especially in the COVID 19 pandemic due to sedentary lifestyle and change in eating habits.  Objective: To determine the consequence that exists between cholesterol levels and physical activity in the Covid-19 pandemic in students of the IV cycle of Obstetrics at Roosevelt University, Huancayo 2021. Material and Methods: It was carried out through the survey technique using the questionnaire, biochemical analysis of cholesterol; Excel and the SPSS version 23 program were used for processing, correlational study. Results: The results obtained in a sample of 36 students, by Spearman's Rho is 0.645, which means that there is a moderate influence between the two variables with a considerable relationship between cholesterol and physical activity in the Covid-19 pandemic. Conclusions: The study shows that the cholesterol levels found in the biochemical analysis and physical activity have a moderate emission, coinciding with the WHO the importance of physical activity to improve living conditions with adequate cholesterol levels that also reflect the quality of Food. Physical inactivity is one of the main problems and deep confinement of cardiovascular risk due to high cholesterol, obesity, depression, various types of cancer, etc.